MENINGKATKAN PERAN BANK SAMPAH DI RW 19 KELURAHAN MUSTIKAJAYA SOLUSI INOVATIF UNTUK PENGELOLAAN SAMPAH DAN PEMBERDAYAAN EKONOMI MASYARAKAT - Ika Baskara; Menik Indrati; Sophiyanto Wuryan (Universitas Mataram, 2026)
Graha Harapan Housing Complex RW 19 in Mustikajaya Village, Bekasi City, is a residential area with a middle-income socio-economic background, but it has significant potential for community-based waste management. Since 2021, a Waste Bank has been established with the aim of raising public awareness and providing environmental and economic benefits. However, its implementation has been suboptimal due to limited infrastructure, low understanding, and a lack of active community involvement. The goal is to improve the knowledge and skills of Waste Bank administrators in financial administration, recording, and reporting, in order to create a more professional management system. Activity methods include outreach to residents, technical and administrative training, and the application of technology to support efficient Waste Bank management. Activities are continued with mentoring, periodic evaluations, and system strengthening to ensure the program runs independently and sustainably. The implementation of Community Service (PKM) activities at the Berseri 19 Waste Bank went well and according to plan. The PKM team succeeded in establishing formal cooperation with the waste bank administrators and identified the main problem, namely the still manual financial recording. As a solution, a simple financial recording application was developed and tested with the administrators. In addition, outreach programs were conducted for residents, which successfully increased their interest in becoming active customers. These activities also directly involved students, which helped strengthen the participatory and partnership-based approach in the community empowerment program. The PKM activities successfully increased institutional capacity and community participation, and encouraged more effective and sustainable Waste Bank operations.